Sustainability of Angkringan Business in East Lombok: Perspectives of Managers and Employees - Nesi Nirmala (JURNAL PENDIDIKAN IPS, 2025)
Business sustainability is influenced by challenges in a dynamic culinary market. Angkringan in Pringgabaya District, East Lombok, provides economic opportunities for the community and provides affordable consumption options. This research aims to explore the views of managers and employees on the sustainability of the angkringan business, and what are the strategies in dealing with external challenges such as fierce competition, fluctuations in raw material prices, and seasonal dependence, as well as internal challenges in the form of limited capital and labor. This study uses qualitative, descriptive, and analytical research. How to obtain data through observation, in-depth interviews, and documentation. The results of this study show that strategies such as product diversification, technology utilization, and operational efficiency show great potential in maintaining sustainability. The adoption of technology can increase production, expand the market, and improve efficiency. With the right strategy and external support, angkringan in Pringgabaya has the potential to survive and grow.